Vaccine hesitancy and knowledge regarding maternal immunization among reproductive age women in central Italy: a cross sectional study - Moschese, Viviana; De Angelis, Luigi; Capogna, Maria Vittoria; Graziani, Simona; Baglivo, Francesco; Pietropolli, Adalgisa; Miraglia Del Giudice, Michele; Rizzo, Caterina; , the Italian Society of Pediatric Allergology and Immunology (SIAIP) Vaccine Committee; Moschese, V.; Beni, A.; Costagliola, G.; et al. (Frontiers in Global Women's Health, 2023)
Background Vaccination in pregnancy offers protection to the mother and the newborn. In Italy, influenza, pertussis, and COVID-19 vaccinations are recommended in pregnancy, but vaccination coverage is still far from the National Immunization Plan goals. We aimed to assess knowledge and attitude on maternal immunization in two groups of Italian women, in pregnancy and in reproductive age (non pregnant). Methods A cross sectional study on Italian childbearing age women gathering information on their knowledge on maternal immunization and attitudes to receiving influenza and pertussis vaccines in pregnancy was carried out at the University of Rome Tor Vergata, between September 2019 and February 2020. Logistic and multinomial regressions were chosen as statistical tests for our analysis. Results 1,031 women participated in the survey by answering the questionnaire. Out of these, 553 (53.6%) women were pregnant, and 478 (46.4%) were in the reproductive age. 37% (204/553) of pregnant women and 41% (198/476) of non pregnant women are aware of the existence of an immunization plan for pregnant women in Italy. The group with age between 20 and 30, for both pregnant women and women in the reproductive age, has a better knowledge of vaccination in pregnancy. Working status is a variable associated with more awareness about vaccination during pregnancy only for pregnant women (OR = 2.34, p < 0.00001). Educational status, trimester of pregnancy and knowledge on the topic are associated with vaccine hesitancy in our multivariate analysis for pregnant women. In the reproductive age group women who had a previous pregnancy are more likely to be hesitant towards vaccination in pregnancy, on the other hand the one with a higher knowledge and educational status are more likely to get vaccinated. Conclusions The study highlights the persistent vaccine hesitancy among Italian women of reproductive age and pregnant women. Despite healthcare providers being identified as a reliable source of information, their recommendations alone are insufficient to overcome vaccine hesitancy. Factors such as employment status, educational level, pregnancy trimester, and knowledge about vaccinations during pregnancy influence vaccine hesitancy. Tailored educational interventions and communication campaigns targeting these areas can help reduce vaccine hesitancy and promote maternal immunization.